High-throughput CRISPR technology: a novel horizon for solid organ transplantation - Li, Xiaohan; Chen, Zhang; Ye, Weicong; Yu, Jizhang; Zhang, Xi; Li, Yuan; Niu, Yuqing; Ran, Shuan; Wang, Song; Luo, Zilong; Zhao, Jiulu; Hao, Yanglin; et al. (Frontiers in Immunology, 2024)
Organ transplantation is the gold standard therapy for end-stage organ failure. However, the shortage of available grafts and long-term graft dysfunction remain the primary barriers to organ transplantation. Exploring approaches to solve these issues is urgent, and CRISPR/Cas9-based transcriptome editing provides one potential solution. Furthermore, combining CRISPR/Cas9-based gene editing with an ex vivo organ perfusion system would enable pre-implantation transcriptome editing of grafts. How to determine effective intervention targets becomes a new problem. Fortunately, the advent of high-throughput CRISPR screening has dramatically accelerated the effective targets. This review summarizes the current advancements, utilization, and workflow of CRISPR screening in various immune and non-immune cells. It also discusses the ongoing applications of CRISPR/Cas-based gene editing in transplantation and the prospective applications of CRISPR screening in solid organ transplantation.